A new strategy for edible vegetable oil production. Issue 1 (8th January 2013) - Turkay, Selma; Gurbuz, Hale
Abstract Consumer preference has changed rapidly from refined oils towards virgin oils in recent years. Virgin oils are edible vegetable oils obtained by mechanical procedures, such as expelling or pressing from oil seeds, and are consumed without being refined. Such oils are considered as specialty oils, because only small and medium size mills produce them in small amounts for gourmet and health markets from very different oil seeds. To meet consumer demands, bulk production of virgin oils should be accomplished from commodity oil seeds, such as rapeseeds, at reasonable prices. For this purpose two challenges have to be solved: production of high quality oil seeds, and production of virgin oils with a higher oil yield. In this article we focus on the pre‐treatment processes of oil seeds to increase oil yield, and describe a new alternative process, ultrasound‐assisted alcoholic treatment of oil seeds.